2021
DOI: 10.3390/ijerph18031167
|View full text |Cite
|
Sign up to set email alerts
|

Parent Emigration, Physical Health and Related Risk and Preventive Factors of Children Left Behind: A Systematic Review of Literature

Abstract: The aim of our study was to systematically review the literature on physical health and related consequences of internal and international parental migration on left-behind children (LBC). This review followed PRISMA guidelines. We searched the PubMed, Web of Science, Academic Search Complete, PsycINFO, and Cochrane databases and included studies reporting physical health-related outcomes of children affected by parental migration. The quality of the studies was assessed using the Quality Assessment Tool for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
(90 reference statements)
1
11
0
Order By: Relevance
“…In the literature, growing-up with absent parents is referred to as transnational childhood [ 56 ]. Congruent with our findings, several systematic literature reviews suggest the following health issues to be prevalent among LBC: sadness, worries, anxiety, depression, loneliness, poor nutrition [ 9 , 10 , 24 , 57 , 58 ]. Separation and stress are also reflected in studies on LBC from Kyrgyzstan [ 59 ], from Sri Lanka [ 60 ], and from the Philippines [ 61 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the literature, growing-up with absent parents is referred to as transnational childhood [ 56 ]. Congruent with our findings, several systematic literature reviews suggest the following health issues to be prevalent among LBC: sadness, worries, anxiety, depression, loneliness, poor nutrition [ 9 , 10 , 24 , 57 , 58 ]. Separation and stress are also reflected in studies on LBC from Kyrgyzstan [ 59 ], from Sri Lanka [ 60 ], and from the Philippines [ 61 ].…”
Section: Discussionsupporting
confidence: 71%
“…In literature, families divided across borders are called transnational families, while the notion itself is called transnationalism [6][7][8]. Left-behind children (LBC) is the term commonly used to address the left children of both, internal and international migrant workers [9][10][11]. Another term increasingly used in transnational family literature is staying behind children [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of rural migrant workers have to leave their children living in their hometown due to the high cost of living in urban cities and huge barriers to education and healthcare, resulting in the “left-behind children” phenomenon. Based on the available literature, left-behind children (LBC) are those aged 18 or below who continue to live in their hometown when one or both parents migrate to cities for work for at least 6 months ( 21 , 22 ). According to a national survey conducted by the China Women's Federation in 2013, more than 60 million children in rural China are left behind, accounting for more than one-third of rural Chinese children and more than one-fifth of the entire population of children in China.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the evidence of these behavioral risks varied in different migrant parents. For instance, a recent literature review generalized that BLBC were more likely than those left behind by one or neither parent to engage in smoking and drinking (26). Still, other research suggested that both BLBC and MLBC had a more increased likelihood of smoking than NLBC (27).…”
Section: Introductionmentioning
confidence: 99%